Attitudes towards female genital cutting among pregnant women in Owo, Nigeria - C.O. Omolase; O.O. Akinsanya; S.O. Faturoti; R.S. Omotayo; B.O. Omolase (South African Family Practice)
Background: This study aimed to determine the attitudes of pregnant women attending the antenatal clinic at Federal Medical Centre, Owo, Ondo State, Nigeria, towards female genital cutting.